APPLICATION OF FOSSIL AND ARTEFACT COLLECTION IN THE HUMAN RESERVATION CENTER SANGIRAN OF SRAGEN KRIKILAN CLUSTER BASED ON ANDROID - Susena, Edy; Pamungkas, Canggih Ajika; Khotimah, Nurul (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
Sangiran is the biggest early man site in Indonesia which has an important value such as human evolutions, culture, early fauna, and its environments. The evidence of the living past of early man sees through fossil collection, artifact, and environment. Sangiran collections save in Sangiran Early man Museum, under the management of the Preservation Center of Early Man Site Sangiran. Sangiran site is recognized as a World Cultural Heritage that has a problem in disseminating information about its important value. There are still many people who don't know about the important value of Sangiran.Related to the problem, the writer arranges an application that aims to make it easy for the community in getting information about the collection in the Preservation Center of Early Man Site Sangiran quickly, simple, and informative. This application is designed with the Unified Modeling Language (UML) method. In making this application, the writer uses software Construct 2 that is editor of game HTML5 based developed by Scirra Ltd who maximizes the editor's visual function and behavior-based logic system.The result of the research, the writer makes a mobile informative system that is "Application of the Introduction of Fossil and Artefact Collection in the Preservation Center of Early Man Sangiran Site Cluster Krikilan Based on Android". The advantage of this system is it can be an introduction media by the Preservation Center of Early Man Site Sangiran which only used with Android, meanwhile the weakness is it can only be operated on Android, not yet able to ios and desktop.